2015
DOI: 10.1115/1.4030823
|View full text |Cite
|
Sign up to set email alerts
|

Verification Benchmarks to Assess the Implementation of Computational Fluid Dynamics Based Hemolysis Prediction Models

Abstract: As part of an ongoing effort to develop verification and validation (V&V) standards for using computational fluid dynamics (CFD) in the evaluation of medical devices, we have developed idealized flow-based verification benchmarks to assess the implementation of commonly cited power-law based hemolysis models in CFD. Verification process ensures that all governing equations are solved correctly and the model is free of user and numerical errors. To perform verification for power-law based hemolysis modeling, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 3 publications
3
31
0
2
Order By: Relevance
“…Hariharan, et al found dependence of the ratio of predicted hemolysis between the original and linearized methods on the exponent of duration of exposure for fully developed non‐Newtonian pipe flow, which satisfies issue 1. While they did not recognize the error in the Garon & Farinas source term, this dependence confirms the inconsistency (issue 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hariharan, et al found dependence of the ratio of predicted hemolysis between the original and linearized methods on the exponent of duration of exposure for fully developed non‐Newtonian pipe flow, which satisfies issue 1. While they did not recognize the error in the Garon & Farinas source term, this dependence confirms the inconsistency (issue 2).…”
Section: Discussionmentioning
confidence: 98%
“…Some of these are based on a linearized damage function and, therefore, suffer from problems related to issues 1 and 2 identified here for the Eulerian approach. A common finding among Lagrangian and Eulerian models is that predicted hemolysis differs from measured hemolysis by orders of magnitude, thus additional modeling challenges beyond the mathematical validity issues raised in this article remain to be resolved by future research.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated pipe has the radius and length of 2.5 and 400 mm, respectively (39). The pipe flow is investigated since it has an analytical solution for Eulerian-based hemolysis model in the laminar flow regime.…”
Section: Devicesmentioning
confidence: 99%
“…De um modo geral, em relação aos modelos para quantificação de hemólise, principalmente aos modelos baseados em lei de potências, haja visto que a grande maioria das publicações até o presente mostram simulações computacionais que ou os utilizam diretamente ou então utilizam modelos aperfeiçoados mas derivados deles, pode-se observar um ponto de deficiência que reside no fato de eles incorporarem relações empíricas construídas a partir de experimentos realizados em condições em que a tensão de cisalhamento é constante ao longo de uma linha de corrente (Hariharan et al, 2015). Os dados experimentais sobre os quais essas re-lações empíricas foram calculadas foram obtidas em viscosímetros com escoamento laminar e campo de tensões uniforme, portanto não capturando as características típicas de um escoamento em dispositivos médicos reais, com campo de tensões variável e exposições temporais mais curtas, e múltiplas, a tensões de cisalhamento relativamente altas em diversos pontos de um mesmo dispositivo.…”
Section: Considerações Finaisunclassified
“…A vantagem do modelo baseado em deformação é que ele pode modelar o processo de relaxamento da membrana viscoelástica da hemácia, o que não é possível usando um modelo baseado em tensão mecânica (Arora et al, 2004), (Chen e Sharp, 2011), (Arwatz e Smits, 2013), (Ezzeldin et al, 2015), (Hariharan et al, 2015).…”
Section: Considerações Finaisunclassified